2022
DOI: 10.1155/2022/8603146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Edaravone Combined with Anticoagulant Therapy on the Serum hs-CRP, IL-6, and TNF-α Levels and Activity of Daily Living in Patients with Acute Cerebral Infarction

Abstract: Objective. To explore the effect of edaravone combined with anticoagulant therapy on the serum hs-CRP, IL-6, and TNF-α levels and the activity of daily living (ADL) in patients with acute cerebral infarction (ACI). Methods. The clinical data of 84 ACI patients treated in our hospital from August 2020 to August 2021 were retrospectively analyzed, and they were divided into the routine group (n = 42) and the combined group (n = 42) according to the order of admission. Both groups were treated with routine clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Inflammation, which is positively correlated with the severity of cerebral infarction, is essential in the pathogenesis and progression of the disease and acts as an independent pathogenic factor for clinical prognosis and disease outcome assessment of patients [ 22 ]. CRP, IL-6, and TNF- α , the most representative markers of inflammatory responses, have a direct relationship with cerebral infarction and have gradually become the indicators that researchers and clinical medical staff focus on and attach importance to [ 23 ]. Our findings revealed statistically reduced inflammatory factors IL-6, TNF- α , and hs-CRP in both groups after treatment, with more obvious decreases in the observation group ( P < 0.05), which suggested that bridging therapy can relieve inflammatory responses in ACI patients and reduce the high expression of inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation, which is positively correlated with the severity of cerebral infarction, is essential in the pathogenesis and progression of the disease and acts as an independent pathogenic factor for clinical prognosis and disease outcome assessment of patients [ 22 ]. CRP, IL-6, and TNF- α , the most representative markers of inflammatory responses, have a direct relationship with cerebral infarction and have gradually become the indicators that researchers and clinical medical staff focus on and attach importance to [ 23 ]. Our findings revealed statistically reduced inflammatory factors IL-6, TNF- α , and hs-CRP in both groups after treatment, with more obvious decreases in the observation group ( P < 0.05), which suggested that bridging therapy can relieve inflammatory responses in ACI patients and reduce the high expression of inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%